Inhibition of fatty acid synthase is protective in pulmonary hypertension. (13th May 2016) - Singh, Neetu; Manhas, Amit; Kaur, Gurpreet; Jagavelu, Kumaravelu; Hanif, Kashif
Abstract : Background and Purpose: In pulmonary hypertension (PH), similar to cancer, there is altered energy metabolism, apoptosis resistance and cellular proliferation leading to pulmonary vascular remodelling. Proliferating cells exhibit higher rate of de novo fatty acid synthesis to provide lipids for membrane formation and energy production. As inhibition of de novo fatty acid synthesis proved protective in cancer experimentally, therefore, it was hypothesized that modulation of de novo fatty acid synthesis by inhibition of fatty acid synthase (FAS) may prove beneficial for PH. Experimental Approach: For in vitro studies, human pulmonary artery smooth muscle cells (HPASMCs) were exposed to hypoxia and to induce PH in vivo, rats were treated with monocrotaline (MCT). FAS was inhibited by siRNA (60 nM) and C75 (2 mg·kg −1, i.p. once a week for 5 weeks) in in vitro and in vivo studies respectively. Results: Increased expression and activity of FAS were observed in hypoxic HPASMCs and lungs of MCT‐treated rats. Inhibition of FAS increased apoptosis and glucose oxidation, but decreased proliferation and markers of autophagy, glycolysis and insulin resistance in hypoxic HPASMCs. It also improved the mitochondrial functions as evident by increased level of ATP and restoration of normal level of ROS and membrane potential of mitochondria. In MCT‐treated rats, FAS inhibition decreased right ventricular pressure, hypertrophy, pulmonary vascular remodelling (increased apoptosis and decreased proliferation of cells) and endothelial dysfunction in lungs. Conclusions: Our results demonstrate that FAS activity is modulated in PH, and its inhibition may provide a new therapeutic approach to treat PH.